Lean–Visual Management Integration in Hospital Information Systems to Sustain Pharmacy Performance Under High Workload - Chintya Puspa Ayu Tirta; Merita Arini (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Hospital pharmacy services face increasing operational complexity, requiring efficient, adaptive, and data-driven systems. Integrating Lean Thinking (LT) and Visual Management (VM) into Hospital Information Systems (HIS) offers strategic potential to enhance workflow transparency, reduce waste, and improve service quality. This study aimed to evaluate the impact of LT–VM within HIS on service effectiveness, measured through prescription response times, and process efficiency, measured using the Value Added Ratio (VAR) derived from Value Stream Mapping (VSM). Methods: A quantitative case study was conducted in the outpatient pharmacy unit of PKU Muhammadiyah Wonosobo Hospital, Central Java, Indonesia. Secondary data of 55,767 outpatient prescriptions were analyzed (17,373 pre-implementation and 38,394 post-implementation), while primary data were collected through direct workflow observation using VSM. Statistical analysis used the Mann–Whitney U test to assess pre-post differences, while process efficiency was examined through VAR calculations for compounded and non-compounded prescriptions. Results: Non-compounded prescriptions showed a significant improvement in response time (p = 0.005), despite a 2.5-fold increase in prescription volume, indicating sustained system performance. Notably, unlike most Lean studies that emphasize waiting-time reduction, the present findings demonstrate that LT–VM–HIS integration primarily contributed to maintaining workflow stability under increased workload. Compounded prescriptions exhibited no significant change (p = 0.424), although reduced variability suggested improved consistency. VSM results showed VAR of 40.08% for non-compounded and 51% for compounded prescriptions, highlighting persistent bottlenecks during workflow transitions and the limited influence of digital interventions on labor-intensive manual tasks. Conclusion: The integration of LT–VM within HIS enhanced process consistency, reduced variability, and maintained operational performance under increased workload. However, manual compounding tasks limited efficiency gains, underscoring the need for hospital-wide Lean digitalization and synchronized scheduling to balance demand and capacity. These findings support the broader application of Lean-based digital transformation to achieve resilient and patient-centered healthcare systems.